Alcohol and Risk of Breast Cancer in Postmenopausal Women: An Analysis of Etiological Heterogeneity by Multiple Tumor Characteristics. Issue 7 (22nd August 2014) - Falk, Roni T.; Maas, Paige; Schairer, Catherine; Chatterjee, Nilanjan; Mabie, Jerome E.; Cunningham, Christopher; Buys, Saundra S.; Isaacs, Claudine; Ziegler, Regina G.
Abstract : Alcohol consumption is an established risk factor for breast cancer. Whether associations vary by specific tumor characteristics independent of other characteristics is unclear. We evaluated the association between alcohol consumption and breast cancer risk in the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial cohort (54, 562 women aged 55–74 years recruited at 10 US screening centers between 1993 and 2001; median follow-up, 8.9 years; 1, 905 invasive breast cancer cases). Hazard ratios and 95% confidence intervals for subtypes defined by histological type and estrogen receptor (ER)/progesterone receptor (PR) status were calculated with standard Cox models. A novel 2-stage Cox model assessed heterogeneity in risk for individual tumor characteristics while adjusting for others. Significant trends across categories of alcohol consumption were observed, with hazard ratios for those consuming 7 or more drinks per week versus never drinkers as follows: for estrogen receptor–positive (ER+) cancer, 1.48 (95% confidence interval (CI): 1.19, 1.83); for progesterone receptor–positive (PR+) cancer, 1.64 (95% CI: 1.31, 2.06); for ER+/PR+ cancer, 1.63 (95% CI: 1.30, 2.05); and for mixed ductal/lobular cancer, 2.51 (95% CI: 1.20, 5.24). For ER+ and PR+ cancers, trends were significant for ductal and mixed ductal/lobular types. PR status explained the positive association with ER status (for ER status, P heterogeneity = 0.70 after adjustment for PR status). Alcohol consumption was not associated with all breast cancer subtypes. Future work should emphasize large collaborative studies, precise definition of subtypes, and adjustment for correlated tumor characteristics.